2015
DOI: 10.3390/md13106210
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulative Activity of Low Molecular Weight Chitosans in RAW264.7 Macrophages

Abstract: Chitosan and its derivatives such as low molecular weight chitosans (LMWCs) have been reported to exert many biological activities, such as antioxidant and antitumor effects. However, complex and molecular weight dependent effects of chitosan remain controversial and the mechanisms that mediate these complex effects are still poorly defined. This study was carried out to investigate the immunostimulative effect of different molecular weight chitosan in RAW264.7 macrophages. Our data suggested that two LMWCs (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
30
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 43 publications
5
30
1
3
Order By: Relevance
“…Our results show that chitosan stimulated BMM ROS production with a peak after 4 h and led to significant increases in the TNF-␣ and NO production after 24 h in a bell-shaped response. Similar findings have been reported showing that HMW chitosan had an in vitro stimulatory effect on NO production in PEMs (from male rats) (25) and LMW chitosan stimulated RAW264.7 macrophage TNF-␣ production (24). Another study demonstrated that LMW chitosan induced ROS production in an epithelial, human breast cancer cell line (53).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our results show that chitosan stimulated BMM ROS production with a peak after 4 h and led to significant increases in the TNF-␣ and NO production after 24 h in a bell-shaped response. Similar findings have been reported showing that HMW chitosan had an in vitro stimulatory effect on NO production in PEMs (from male rats) (25) and LMW chitosan stimulated RAW264.7 macrophage TNF-␣ production (24). Another study demonstrated that LMW chitosan induced ROS production in an epithelial, human breast cancer cell line (53).…”
Section: Discussionsupporting
confidence: 85%
“…An indirect mechanism of action may be related to the known proinflammatory effect of chitosan on macrophages. This involves stimulation of tumor necrosis factor alpha (TNF-␣), IL-6, NO, ROS, and IFN-␥, which play critical roles in the proinflammatory response against intracellular microbes by enhancing the production of microbicidal reactive nitrogen species (21)(22)(23)(24)(25). Chitosan activates polymorphonuclear leukocytes, macrophages, and fibroblasts, and these properties promote wound healing (18,26).…”
mentioning
confidence: 99%
“…The obtained results could be attributed to Chitosan, which was confirmed to partially inhibit the secretion of both TNF-α and IL-8 from mast cells reducing the allergic inflammatory response, so chitosan nutraceuticals may help to prevent or alleviate some of these complications [68]. Furthermore, low molecular weight chitosan is capable of decreasing the production of the inflammatory cytokines TNFα and IL-6 [69].…”
Section: Discussionmentioning
confidence: 88%
“…The immune function is recognized to be vital for the prevention and control of infection and abnormal cell growth (Cian, López‐Posadas, Drago, Medina, & Martínez‐Augustin, ). Immune compromise may lead to the developments of certain tumors as well as suppress cancer patient's recovery (Wu et al., ). Macrophages play a major role in regulating inflammation and host defenses, which are activated by lipopolysaccharides (LPS), inflammatory mediators, and cytokines (Je, Cho, & Ahn, ; Reddy & Reddanna, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, hyperactivation of macrophages may have harmful effects, including multiple organ dysfunctions and death, and can also lead to proinflammatory reaction persistence, resulting in chronic inflammatory diseases (Kim, Ahn, & Je, ; Valledor, Comalada, Santamaria‐Babi, Lioberas, & Celada, ). Through stimulating innate immune responses, macrophages initiate cell resistance to inflammation and infection (Wu et al., ). Therefore, regulating activated macrophages is an effective means of evaluating the efficacy of some antitumor and immunomodulatory bioactive compounds (Kim et al., ; Wu et al., ).…”
Section: Introductionmentioning
confidence: 99%